2020
DOI: 10.3390/d12090332
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Diversity and Composition of Bats in a Regenerating Neotropical Dry Forest

Abstract: This study evaluated the response of bat communities, from a taxonomic and functional perspective, to variation in the vegetation and landscape attributes produced by anthropogenic activities. We characterized the following: (1) the community of phyllostomid and mormoopid bats associated with the initial successional stages of a tropical dry forest, (2) the response of these communities to the variation in the attributes of the vegetation and the landscape, and (3) how the seasonality modulates such response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…To broaden the implications of our findings, we defined clutter‐tolerant and intolerant guilds based on similarities in bat morphological characteristics. The clutter‐tolerant guild groups bat species that share a similar suite of morphological and acoustic characteristics (Pettit & Wilkins, 2012; Sleep & Brigham, 2003), allowing them to preferentially access resources in dense vegetation and avoid more open habitats (Martínez‐Ferreira et al, 2020; Nkrumah et al, 2016; Sleep & Brigham, 2003). Because clutter‐tolerant species have relatively small home ranges within spatially complex vegetation assemblages, induced habitat changes may affect the extent of expected ecological services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To broaden the implications of our findings, we defined clutter‐tolerant and intolerant guilds based on similarities in bat morphological characteristics. The clutter‐tolerant guild groups bat species that share a similar suite of morphological and acoustic characteristics (Pettit & Wilkins, 2012; Sleep & Brigham, 2003), allowing them to preferentially access resources in dense vegetation and avoid more open habitats (Martínez‐Ferreira et al, 2020; Nkrumah et al, 2016; Sleep & Brigham, 2003). Because clutter‐tolerant species have relatively small home ranges within spatially complex vegetation assemblages, induced habitat changes may affect the extent of expected ecological services.…”
Section: Discussionmentioning
confidence: 99%
“…preferentially access resources in dense vegetation and avoid more open habitats(Martínez-Ferreira et al, 2020;Nkrumah et al, 2016;Sleep & Brigham, 2003). Because clutter-tolerant species have relatively small home ranges within spatially complex vegetation assemblages, induced habitat changes may affect the extent of expected ecological services.…”
mentioning
confidence: 99%
“…Studies of bat communities in and in response to early successional stages are generally lacking (Mart ınez -Ferreira et al, 2020), and assessing baseline biodiversity of the bat community refuted the assumption that restoration sites are initially species poor prior to the implementation of restoration. Whereas previous studies have found that abandoned pastures and sites in early stages of recovery are characterized by few species with high relative abundance (Avila-Cabadilla et al, 2009;de la Peña-Cu ellar et al, 2015;Medell ın et al, 2000), we found that the phyllostomid (leaf-nosed) bat assemblage was not different in terms of species richness, entropy, nor evenness across forest and restoration sites.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental context, baselines address a potential confounding variable when comparing the outcome of different experimental treatments; this cannot be done from inferring initial stages via cross-sectional studies. Initial assemblages are key to the direction of early succession (in the context of different ecological roles) and are highly variable at the regional scale (Mart ınez -Ferreira et al, 2020).…”
mentioning
confidence: 99%
“…This selection is positively or negatively correlated with the canopy cover and floristic composition of the vegetation stand. Martínez-Ferreira et al (2020) reported that although several bat species can find resources in the secondary forests, they continue to depend on the resources available in old growth forests, which favor great diversity and abundance for bats.…”
Section: Journal Of Sustainability Science Andmentioning
confidence: 99%